2021
DOI: 10.1002/jcla.24147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plasma circ_0006282 as a novel diagnostic biomarker in colorectal cancer

Abstract: Background Nowadays, non‐invasive and rapid detection of cancers through molecular biomarkers has received much attention. Therefore, this study investigated the non‐invasive and rapid diagnosis of colorectal cancer through one of the newest biomarkers (circular RNA). Methods For this purpose, we collected tumoral, adjacent normal tissue, and plasma samples from 100 colorectal cancer (CRC) patients, 25 postoperative CRC patients, 28 colitis patients, and 108 healthy donors. First Illumina high‐throughput (Hi S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Moreover, our findings revealed that plasma levels of hsa_circ_101303 offer moderate diagnostic accuracy for CRC (AUC: 0.738) as determined through RT-qPCR assay. While this aligns with the observations by Radanova et al [ 23 ], our results suggest a slightly lower diagnostic accuracy compared to the studies conducted by Ye et al [ 22 ] and Zhu et al reports [ 24 ]. These collective results highlight the potential of hsa_circ_101303 as a promising diagnostic biomarker for CRC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, our findings revealed that plasma levels of hsa_circ_101303 offer moderate diagnostic accuracy for CRC (AUC: 0.738) as determined through RT-qPCR assay. While this aligns with the observations by Radanova et al [ 23 ], our results suggest a slightly lower diagnostic accuracy compared to the studies conducted by Ye et al [ 22 ] and Zhu et al reports [ 24 ]. These collective results highlight the potential of hsa_circ_101303 as a promising diagnostic biomarker for CRC.…”
Section: Discussionsupporting
confidence: 90%
“…Radanova et al [ 23 ] reported moderated diagnostic values for plasma levels of hsa_circ_0001445, hsa_circ_0003028, hsa_circ_0007915, and hsa_circ_0008717 in CRC, with AUC values of 0.739, 0.693, 0.776, and 0.626, respectively. Furthermore, another study demonstrated that plasma levels of hsa_circ_0006282 hold significant diagnostic potential for CRC, with an AUC of 0.831 [ 24 ]. In our investigation, we observed an upregulation of hsa_circ_101303 in both plasma and tissue samples of CRC, indicating its consistent expression in these compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study revealed that plasma circ_0006282 can differentiate between patients with colorectal cancer and colitis. Taken together, these findings suggest that plasma circ_0006282 can serve as a promising diagnostic and dynamic monitoring biomarker for CRC ( 160 ).…”
Section: Circrna As a Diagnostic Biomarker For Crcmentioning
confidence: 77%
“…Our geneMANIA result indicates the strongest genetic interaction with HSPB6 is ITGA7 [ 52 , 53 ], which has been upregulated in cells derived from embryonic stem cells [ 54 ]. Interestingly, HSPB6 [ 21 ] and ITGA7 [ 55 , 56 ] were downregulated in colorectal cancer, suggesting potential transcriptional positive regulation. In contrast, HSPB1 has the strongest physical interaction with HSPB6 [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%